Web Based Aviation Communication Tool Information System - Erwin Gatot Amiruddin (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
In the field of air transportation, the communication system is used as a means of communication between officers on the ground and pilots or fellow officers on the ground. From this, the author wants to design a communication system as a medium to maintain a more effective and profitable communication system used as an air transportation communication system. This study aims to create an information system for reporting maintenance and repair of Aviation Communication Facility equipment at the Public Company (Perum) LPPNPI Makassar Branch by using the Web to make it easier for technician groups to fill out maintenance and repair reports that previously still used conventional methods which used paper and tools. write in doing data recording and requires space for archiving. The data were obtained through (1) field observations, (2) data requests, (3) literature studies. The method and theory used in making the system is the Waterfall method. The results of this study indicate that the information system of Aviation Communication Facilities can run well. Based on the test results using the Black Box testing technique and UAT testing, the results obtained 85% of the 20 respondents, so it was declared feasible to be used at the research location.